Asclepiadaeum: un poema latino del Perú colonial - Helmer, Ángela (2011)
The role that Latin played as the language of culture and prestige in the Spanish colonies of America has not been studied in depth. Especially, in the case of the viceroyalty of Peru, the lack of documents has prevented detailed research in this area. In this paper I analyze the importance of Latin in urban areas of Peru´s colonial society based on documents written by Peruvian authors and published in the viceroyalty of Peru up to the beginning of the nineteenth century. Among these, and because of its unique nature, the Asclepiadaeum, a poem in honor of the Viceroy de la Pezuela, who arrived in Lima in 1816, stands out